2023
DOI: 10.1002/iid3.992
|View full text |Cite
|
Sign up to set email alerts
|

High systemic immune‐inflammation index is relevant to osteoporosis among middle‐aged and older people: A cross‐sectional study

Suli Zhang,
Wenyan Ni

Abstract: BackgroundAs one of novel inflammatory indexes proposed in recent years, systemic immune‐inflammation index (SII) can comprehensively reflect the inflammatory and immune state of the body. This study aims to explore the relationship between SII and osteoporosis among middle‐aged and older people.Materials and MethodsOur study includes 20,497 individuals from National Health and Nutrition Examination Survey (NHANES) 2005–2008, and target study population are confined to people aged 45 years and above. SII is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Most importantly, SII has been shown in many studies to be more responsive to the body’s inflammatory state and to have greater prognostic value than other inflammatory markers ( 8 , 9 , 33 , 34 ). As previously described, SII was initially used primarily in oncology patients, however, with further research it also is strongly associated with other diseases such as osteoporosis among middle-aged and older people ( 35 ), ulcerative colitis ( 36 ), metabolic syndrome ( 37 ), heart failure ( 38 ), periodontitis ( 16 ), chronic obstructive pulmonary disease ( 14 ), coronary heart disease ( 39 ), hyperlipidemia ( 40 ), cognitive impairment ( 41 ), rheumatoid arthritis ( 42 ) and depression ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, SII has been shown in many studies to be more responsive to the body’s inflammatory state and to have greater prognostic value than other inflammatory markers ( 8 , 9 , 33 , 34 ). As previously described, SII was initially used primarily in oncology patients, however, with further research it also is strongly associated with other diseases such as osteoporosis among middle-aged and older people ( 35 ), ulcerative colitis ( 36 ), metabolic syndrome ( 37 ), heart failure ( 38 ), periodontitis ( 16 ), chronic obstructive pulmonary disease ( 14 ), coronary heart disease ( 39 ), hyperlipidemia ( 40 ), cognitive impairment ( 41 ), rheumatoid arthritis ( 42 ) and depression ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have delved into the association between SII and the incidence as well as mortality rates of fractures and complications across the general populace and diverse patient categories. Zhang et al ( 32 ) reported that there exists an association between increased SII and an increased vulnerability to systemic inflammation as well as osteoporosis in middle-aged and elderly populations. Fang et al ( 33 ) found that monitoring changes in SII could play a role in predicting osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The SII can comprehensively reflect the inflammatory and immune state of the body, as one of the novel inflammatory indexes proposed in recent years. 25 In a previous study by Lu et al, SII was defined as a new index for evaluating immunity and inflammation, which was obtained by the platelet count × neutrophil count/lymphocyte count. Higher SII indicated that patients had stronger inflammation and weaker immune response.…”
Section: Discussionmentioning
confidence: 99%